Cleansing and separation procedures reflect resource concerns. (18th February 2021) - Schnall, Simone; Henderson, Robert K.
Abstract: We propose that procedures of separation have two functions, namely first, to establish the integrity of individual parts, and second, to make previously joint entities discreet and therefore countable. This allows taking stock of available resources, including evaluating the use of individual objects, a process that is especially adaptive under conditions of threat of contagious disease and resource scarcity.